Territorial Authority and Personal Jurisdiction - Arthur M. Weisburd (Washington University Law Quarterly, 1985)
This Article seeks to show that the Supreme Court was correct in its implicit assertion in World- Wide Volkswagen v. Woodson that, given the nature of the federal system, the authority of American states is territorially limited. It further seeks to determine the content of the general territorial limitations on state authority and to deduce the particular limitations that should apply to personal jurisdiction. The Article concludes that the Supreme Court was correct in asserting that the logic of the federal system requires the conclusion that a state may assert jurisdiction only over nonresidents who have liability-related contacts with state territory. The Articles also concludes, however, that the federalism argument does not logically support the requirement that the defendant's contacts be intentional. This Article will achieve its objectives through a three-part discussion. Part I provides a brief description of the development of the law of personal jurisdiction in the United States. In Part II, the Article presents in detail the arguments supporting the conclusions described above. Part III will refute various arguments that have been raised attacking territory-based jurisdictional analysis.
Keywords: Personal jurisdiction